ANALISIS MODEL PEMBELAJARAN INOVATIF TERHADAP PARTISIPASI AKTIF SISWA PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Anissa Salsabila Wirdani; Rhaffy Hendrika Prasetiohadi; Shofiatul Muawanah; Muhammad Imaduddin; Arif Mahya Fanny (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In teaching and learning activities at school, teachers often face various challenges related to student engagement in the classroom, particularly in the learning process at the elementary school level. This indicates that education must continue to evolve in order to meet the diverse needs of students that arise over time. This situation is also one of the challenges faced by teachers in the learning process at the elementary school level. Therefore, all teachers are obligated to possess the ability to manage learning effectively to create a meaningful learning environment, and one way to do this is by implementing innovative learning models. This study aims to analyze the relationship between the implementation of innovative learning models and students’ active participation in IPAS (Science) lessons in the fourth grade at Suratmajan Public Elementary School. This study is a descriptive-evaluative study using a qualitative approach supported by simple data collection obtained through the distribution of Likert-scale questionnaires. The data collection techniques employed included observation, teacher interviews, the distribution of questionnaires to all students, and documentation. The data obtained was then reanalyzed descriptively to identify the relationship between the implementation of innovative learning models and student participation. Through the observation and data analysis conducted, the results of this study demonstrate and confirm that the implementation of innovative learning models is effective in enhancing student participation in the learning process, as evidenced by increased student engagement in asking questions, answering, and discussing in groups.